2022
DOI: 10.1097/ta.0000000000003585
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital activation of a coordinated multidisciplinary hospital response in preparation for patients with severe hemorrhage: A statewide data linkage study of the New South Wales “Code Crimson” pathway

Abstract: Prehospital medical teams accurately alert trauma teams of the impending arrival of severely injured patients requiring massive blood transfusion and interventional hemorrhage control using “Code Crimson” activations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…For air-type PICUs, HEMS is the most common type that was reported in nine studies from Australia, Germany, Denmark, France, and Japan. Some articles reported HEMS alone [29,30,33,34,38], while four articles mentioned HEMS operating in combination with GEMS [26][27][28]36].…”
Section: Type and Size Of The Picumentioning
confidence: 99%
See 1 more Smart Citation
“…For air-type PICUs, HEMS is the most common type that was reported in nine studies from Australia, Germany, Denmark, France, and Japan. Some articles reported HEMS alone [29,30,33,34,38], while four articles mentioned HEMS operating in combination with GEMS [26][27][28]36].…”
Section: Type and Size Of The Picumentioning
confidence: 99%
“…Moreover, providers were trained to provide basic or intermediate care to trauma patients, such as oxygen administration, vascular access, and defibrillation [33,39]. The most reported advanced skill training includes advanced airway management, cricothyroidotomy, and advanced life support training [27,29,30,37,39]. In addition, some ICFPs had additional qualifications or skills to perform advanced care such as intubation or blood transfusion [30,33,34,39].…”
Section: Trainingmentioning
confidence: 99%
“…Red Blanket, pre‐hospital Code Crimson, in‐hospital Code Crimson and OPSTAT are all protocols that are used for the management of the exsanguinating patient 1–6 . In Australasia they have been heavily communicated but varyingly adopted by providers of trauma care.…”
mentioning
confidence: 99%
“…Partyka et al . in their data linkage paper describing the pre‐hospital Code Crimson guideline implemented in NSW very appropriately highlighted many of the limitations of these types of studies; they clearly identified the inability to make an obvious clinical benefit from pre‐hospital Code Crimson and acknowledged the need for prospective clinical trials 2 . Similarly, Tovmassian and colleagues were unable to demonstrate improved outcomes, also recognizing the need for larger RCT; however, they were able to show decreased time to operating room for their in‐hospital Code Crimson 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation